International Labour Migration to Europe's Rural Regions - Rye, Johan Fredrik; O'Reilly, KAREN (Routledge Advances in Sociology, 2021)
"Emerging in the throes of a global pandemic that threatens Europe's economies and food security, International Labour Migration to Europe's Rural Regions combines a diverse range of empirically rich, in-depth case studies, analysis of their rural context specificities, and insights from labour market and migration theories, to critically examine the conditions and implications of rural labour migration. Despite its growing political, economic and social importance, our understanding of international labour migration to Europe's rural regions remains limited. This edited volume provides intricate descriptions of lived experience, critical theoretical analyses, analytical synthesis, and policy recommendations for this novel and developing phenomenon that has the potential to transform the lives of international migrants and local communities. The book's 25 authors represent a wide range of social science disciplines, with coverage of a vast range of Europe's rural regions, and diverse types of rural labour in areas such as horticulture, shepherding, wild berry picking and fish processing. The volume will be of interest to policy makers at local, regional, national and European levels, and scholars and students in a broad range of areas, including migration, labour markets, and rural studies. "